Desarrollo y estabilidad vascular : implicancias en el síndrome de hiperestimulación ovárica (OHSS) - Scotti, Leopoldina (2015)
Ovarian hyperstimulation syndrome (OHSS) is a severe complication of ovarian\nstimulation with gonadotropins in assisted reproductive techniques. In OHSS, hCG\nstimulates an overproduction of vascular endothelial growth factor (VEGF), the main\nresponsible for the increase in vascular permeability. This produces edema, ascites, and\nin severe cases, pulmonary and renal failure. However, in addition to VEGF, other\nsystems are involved in the regulation of vascular permeability. Based on this\nknowledge, the following hypotheses were proposed:\n* Inhibition of VEGF or Angiopoietin system (ANGPTs) in OHSS affects ovarian\nangiogenesis, decreasing the vascular permeability that leads to the development of\nascites and therefore, improves ovarian function.\n* S1P levels are decreased in patients at risk of developing OHSS, being partly\nresponsible for the high vascular permeability observed in these patients.\nThe results of this Thesis provide knowledge to elucidate the etiology of OHSS\nand to detect biomarkers (VEGF, ANGPT-1, S1P) that could be used to prevent the\ndevelopment of OHSS and to help doctors to choose the best strategy for ovarian\nstimulation for each patient.